Ekspor Karet Indonesia ke-15 Negara Tujuan Utama Setelah Pemberlakuan Kebijakan ACFTA - Lembang, Marlina Banne; Pratomo, Yulius (TRIKONOMIKA, 2013)
The objective of this study is to examine factors affecting Indonesia’s rubber export performance to Indonesia’s 15 main trading partners after the implementation of ACFTA. This research employs Bergstrand Gravity Model (1985) using 105 observation for 15 countries from 2004 to 2010. Then, the gravity model is estimated by applying random effects (RE) model. The results show that, first, GDP per capita of Indonesia’s main trading partners have significantly positive impact on export. Surprisingly, distance has significantly positive effect on Indonesia’s rubber export. Further, Indonesia’s rubber major export destinations are the member of ACFTA, i.e. China and Singapore. Last, some of the non member countries are still potential to be Indonesia’s rubber market. Therefore, the Government of Indonesia should increase trading with them.